PENGEMBANGAN LKPD BERBASIS CHEMO-EDUTAINMENT KELARUTAN DAN HASIL KALI KELARUTAN SMA NEGERI 1 MANDOR - Rachma Daniyati; Tuti Kurniati; Rizmahardian Ashari Kurniawan (Jurnal Ilmiah Ar-Razi, 2020)
This development research is motivated by the low learning outcomes of students and the lack of motivation students in learning chemistry, especially on solubility and solubility result at SMAN 1 Mandor. This study aims to produce worksheets based on chemo-edutainment student on solubility and solubility result. This type of research is the development of the ADDIE Research and Development (R&D) model. The instruments used were validation sheets, questionnaire sheet for teacher and student responses and test sheets for pretest and posttest questions. The analysis shows the validity criteria obtaine by the validator 1.0 value with a very valid category. The results of the questionaire respons of primary field trial students obtained an average percentage value of 88.57 %. The efective criteria for chemo-edutainment based worksheets were seen from the pretest and posttest results of students calculated using N-gain formula, the value obtained in the main field trial is 0.85 (very high). Based on these results, it can be conculuded that the development of chemo-edutainment based student worksheets is feasible to be used as teaching material on solubility material and solubility results in class XI IPA in SMAN 1 Mandor.